Inside Immigration Law : Migration Management and Policy Application in Germany - Eule, Tobias G. (Research in migration and ethnic relations series., 2014)
Inside Immigration Law analyses the practice of implementing immigration law, examining the different political and organisational forces that influence the process. Based on unparalleled academic access to the German migration management system, this book provides new insights into the 'black box' of regulating immigration, revealing how the application of immigration law to individual cases can be chaotic, improvised and sometimes arbitrary, and either informed or distorted by the complex, politically laden and changeable nature of both German and EU immigration laws.